Analisis Rasio Keuangan untuk Mengukur Kemandirian Keuangan Pemerintah Daerah Kabupaten Sidoarjo Tahun Anggaran 2019-2023 - Maulidia, Dwi Nur; Parikesit Penangsang (Nirta Learning Centre, 2024)
This study aims to analyze financial ratios as a tool to measure the financial independence of the regional government of Sidoarjo Regency during the fiscal years 2019-2023. The data used was obtained from the Sidoarjo Regency Regional Financial and Asset Management Agency (BPKAD). The results of the analysis show that the average financial independence ratio reaches 69.98%, which is included in the participatory category. However, the average dependency ratio of 57.48% indicates a very high level of dependence on external funding. Furthermore, the average efficiency ratio is 106.90%, which means that local governments are not efficient in managing their budgets. Meanwhile, the average fiscal decentralisation ratio of 40.16% is good, indicating the potential to increase financial independence. These findings provide a comprehensive picture for decision-makers to formulate more effective strategies to improve regional financial independence.